Psychosocial criminology - Gadd, David 1975-
Shedding light on explanations of crime, this title demonstrates how a psychosocial approach can illuminate the causes of particular crimes, challenging readers to re-think the similarities and differences between themselves and those involved in crime
Keywords: Criminal psychology; Crime -- Sociological aspects